Biomechanical stability of oblique lateral interbody fusion combined with four types of internal fixations: finite element analysis - Hao, Jiayu; Tang, XianSheng; Jiang, Nizhou; Wang, Hong; Jiang, Jian (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: Using finite element analysis to identify the optimal internal fixation method for oblique lateral lumbar interbody fusion (OLIF), providing guidance for clinical practice.: A finite element model of the L4 -L5 segment was created. Five types of internal fixations were simulated in the generated L4-L5 finite element (FE) model. Then, six loading scenarios, i.e., flexion, extension, left-leaning, right-leaning, rotate left, and rotate right, were simulated in the FE models with different types of fixations. The biomechanical stability of the spinal segment after different fixations was investigated. RESULTS: Regarding the range of motion (ROM) of the fused segment, OLIF + Bilateral Pedicle Screws (BPS) has a maximum ROM of 1.82° during backward bending and the smallest ROM in all directions of motion compared with other models. In terms of the von Mises stress distribution on the cage, the average stress on every motion direction of OLIF+BPS is about 17.08MPa, and of OLIF + Unilateral Vertebral Screw -Pedicle Screw (UVS-PS) is about 19.29MPa. As for the von Mises stress distribution on the internal fixation, OLIF + BPS has the maximum internal fixator stress in left rotation (31.85 MPa) and OLIF + Unilateral Pedicle Screw (UPS) has the maximum internal fixator stress in posterior extension (76.59 MPa). The data of these two models were smaller than those of other models. Conclusion: OLIF+BPS provides the greatest biomechanical stability, OLIF+UPS has adequate biomechanical stability, OLIF + UVS-PS is inferior to OLIF + UPS synthetically, and OLIF + Double row vertical screw (DRVS) and Individual OLIF (IO) do not present significant obvious advantages.